(untitled) (Bangladesh Journal of Medical Microbiology, 2024)
Background: Acinetobacter baumannii infection treatment has become a clinical challenge due to the increasing resistance of the bacteria to different classes of antimicrobial agents and it needs to be identified before exposure to patients. Objective: This study aimed to determine the prevalence of Acinetobacter baumannii with its antibiotic-resistant patterns. Methodology: The study was a cross-sectional study that was done from 1st January 2019 to 31st December 2019 at the Microbiology Department of Dhaka Medical College. Clinical samples including endotracheal aspirates, blood, urine, sputum, wound swabs, and pus were collected from the patients from the intensive care unit, burn unit, general wards, and outpatient department of Dhaka Medical College and Hospital. Acinetobacter baumannii organisms were identified by biochemical tests and Gram staining, and the resistance pattern was determined by using the disc diffusion method for all antibiotics except for colistin, which was determined by minimum inhibitory concentration. Results: Among 500 clinical samples, 13.31% Acinetobacter baumannii were identified. Most of these showed resistance to fluoroquinolones, carbapenem, amikacin, the extended spectrum of cephalosporin, β-lactam, and β-lactamase inhibitors. However, the least resistant drug was tigecycline (8.88%). About 62.22% MDR, 28.89% A. baumannii were identified. Conclusion: Acinetobacter baumannii is showing increasing resistance to colistin and tigecycline. Bangladesh Journal of Medical Microbiology, January 2024;18(1):37-43